Penyelesaian Tindak Pidana Penganiayaan Melalui Kearifan Lokal di Kabupaten Muaro Bungo - Hidayat, Iman (Universitas Batanghari Jambi, 2025)
Humans as social creatures, in interacting with each other and with other creatures, are bound by laws that regulate what they can do and what they cannot do. The increase in crimes of assault encourages us to pay more attention to preventing and handling them. Abuse is a crime and the perpetrator can be brought to court, even if it occurs in a hamlet. The police actually have the right to enter a hamlet where there is a commotion and the abuse is not a complaint offense. The peace process for criminal acts of abuse in Muaro Bungo Regency began with a complaint or report or agreement from both parties involved in a case of criminal abuse to the Head of the Traditional Institution, in the form of submitting a sign of obedience, the contents of which are that both the perpetrator and the victim agree to resolve the case in question through customary law. Which sign of obedience is submitted to the customary institution which will resolve the case of criminal abuse based on the severity of the consequences of the criminal act of abuse that arose. Then, after the sign of obedience is received by the head of the customary institution which will handle the case, it is immediately followed up by holding a deliberation so that the case in question is resolved quickly. The person who acts as a mediator or leader of the session is the head of the customary institution or the person who knows the most about the provisions of customary law, especially criminal cases, which is attended by customary leaders, community leaders, religious scholars, and intellectuals so that the decision taken feels fair to all